Biaxial orientation polyester film
By adopting biaxial orientation technology and design of A1/B/A2 three-layer polyester resin layer in polyester films, combined with the combination of modified polyester and inorganic fillers, the heat of the polyester film in high temperature and high frequency environment is solved. Performance and surface scratch/scratch problems have achieved efficient and economical film performance improvement.
Patent Information
- Application Number
- CN202411877368.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-12-18
Smart Images

Figure BDA0005197446430000211 
Figure BDA0005197446430000221
Abstract
Description
Technical Field
[0001] The invention belongs to a polyester film, in particular to a biaxially oriented polyester film. Background Art
[0002] Polyethylene terephthalate (PET), chemical formula is (C 10 H 8 O 4 ) n It is made by exchanging dimethyl terephthalate with ethylene glycol or by esterifying terephthalic acid with ethylene glycol to synthesize dihydroxyethyl terephthalate, and then polycondensing it. It has excellent physical and mechanical properties in a wide temperature range and excellent electrical insulation; even at high temperature and high frequency, its electrical properties are still good, and its creep resistance, fatigue resistance, friction resistance and dimensional stability are all very good. PET materials can be used in different fields, such as spinning, engineering plastics, films, etc., by being processed in different ways. Polyester film is made of polyethylene terephthalate material through melt co-extrusion and biaxial stretching. Due to its good mechanical properties, thermal properties, electrical insulation and optical properties, it has a wide range of applications.
[0003] The BOPET industry is booming. As the world's polyester film production base, China has a total production capacity of nearly 5.5 million tons. Polyester film has a wide range of applications. Although China's polyester film production is huge, it is mainly used in the middle and low-end. Compared with the polyester films of Japan and South Korea, there is still a gap and it cannot meet the real needs of customers. This has caused a prominent structural contradiction in my country's polyester film industry - ordinary films are saturated and oversupplied, and high-end polyester films rely on imports, with an annual import volume of 200,000 to 300,000 tons. This is mainly reflected in the unstable quality of domestic polyester films, or the quality is difficult to meet the requirements of downstream industries. Especially when used in aluminum-plated films, release films for ceramic capacitors, IMD, plate glazing, high-end release films, satellite thermal control films and other fields, there are extremely high requirements for film thermal properties and film surface scratches / scratches. Taking the well-known release film for ceramic capacitors as an example, the ceramic capacitor manufacturing process is roughly divided into two steps: one is the ceramic slurry casting (the ceramic slurry is passed through the pouring port of the casting machine to be coated on the bypassing PET release film and dried in the conventional hot air zone); the second is to print the electrode on the formed ceramic sheet, then tear off the release film, and then sinter at high temperature. The PET release film here is a release film for ceramic capacitors, that is, the release film is coated on the film substrate for ceramic slurry casting. The quality of the film substrate directly determines the quality of the ceramic sheet; if the polyester film has poor thermal properties, the film surface is uneven when the release layer is coated on the machine, and the release layer is unevenly spread, affecting the uniformity of the ceramic slurry thickness. The appearance of the film will also affect the uniformity of deep processing. If there are scratches / scratches on the surface of the film, the release layer will not spread at the scratches / scratches. When the ceramic slurry is cast downstream, the scratches / scratches cannot be peeled off, and it may even easily cause the ceramic sheet to break. Similarly, the thermal properties and appearance of polyester film restrict its application in the fields of aluminized film, IMD, sheet glazing, high-end insulation film, satellite thermal control film, etc.
[0004] In response to the requirements of many high performances in different fields, the existing technical solutions to solve the problems in the polyester film field are: 1. During the production of polyester film, the temperature of the TDO shaping area is increased to increase the crystallinity of the film and improve the thermal performance of the polyester film. 2. Add larger particles (≥4.0μm) to the surface of the polyester film to increase the smoothness and reduce scratches / scratches on the film surface. 3. During downstream processing, reduce the production speed, reduce tension, and improve the uneven film surface caused by the film passing through the machine.
[0005] Although technicians have conducted a lot of research on polyester film, the current technical solutions to solve the polyester film problem still have many shortcomings: 1. Heating the shaping zone can improve the crystallinity of the film to a certain extent, but the film with high crystallinity is prone to brittleness, which is not conducive to downstream machine passing, and is prone to scratches. It will also cause uneven crystallization of the film and affect the flatness. 2. Adding larger particles (≥4.0μm) to the surface improves the smoothness of the polyester film, but large particles can easily cause the surface of the film to have a strong sense of bumps and bumps. When used in fields with high requirements for surface gloss (such as IMD, sheet glazing), it is difficult to meet their requirements. 3. Reducing the production speed will lead to a decrease in downstream production efficiency and an increase in production costs. Summary of the invention
[0006] The present invention provides a biaxially oriented polyester film, which has the characteristics of excellent thermal performance, no scratches / scratches on the surface, etc., improves product quality, simplifies production process, and reduces production cost. The product can be widely used in many fields such as aluminum plating film, release film for ceramic capacitors, IMD, plate glazing, high-end release film, satellite thermal control film, etc.
[0007] In order to overcome the deficiencies in the prior art, the technical solution adopted by the present invention is as follows:
[0008] A biaxially oriented polyester film comprises three polyester resin layers A1 / B / A2; the A1 layer comprises the following materials in parts by weight:
[0009] Functional masterbatch X10 to 50 parts by weight
[0010] 50 to 90 parts by weight of pure polyester resin;
[0011] The functional masterbatch X comprises the following substances in parts by weight:
[0012] Inorganic filler x 0.3 to 10 parts by weight
[0013] 90 to 99.7 parts by weight of modified polyester,
[0014] Wherein, the inorganic filler x is crystalline spherical silica particles coated with amorphous silica on the surface, and the average particle size is 0.3 μm to 3 μm;
[0015] Layer B includes the following materials in parts by weight:
[0016] Functional masterbatch Y 5 to 40 parts by weight
[0017] 60 to 95 parts by weight of pure polyester resin;
[0018] The functional masterbatch Y is composed of:
[0019] Inorganic filler y 1 to 15 parts by weight
[0020] 85 to 99 parts by weight of modified polyester,
[0021] Wherein, the inorganic filler y is crystalline spherical silica particles with an average particle size of 0.03 μm to 1 μm;
[0022] The A2 layer includes the following materials in parts by weight:
[0023] Functional masterbatch Z 5 to 30 parts by weight
[0024] 70 to 95 parts by weight of pure polyester resin;
[0025] The functional masterbatch Z has the same composition as the functional masterbatch X;
[0026] The modified polyester adopts 4-(3,5-dicarboxyphenoxy)phthalic acid, 4,4-propanediyldioxydibenzoic acid, 3,5-di(p-carboxyphenyl)benzoic acid, and terephthalic acid;
[0027] definition:
[0028] X1 is the content ratio of 4-(3,5-dicarboxyphenoxy)phthalic acid component relative to the total dicarboxylic acid components in the modified polyester;
[0029] X2 is the content ratio of 4,4-propanediyldioxydibenzoic acid component relative to the total dicarboxylic acid components;
[0030] X3 is the content ratio of 3,5-di(p-carboxyphenyl)benzoic acid component relative to the total dicarboxylic acid components;
[0031] X4 is the content ratio of terephthalic acid component to the total dicarboxylic acid components;
[0032] X1, X2, X3, and X4 satisfy the following relationship:
[0033] 5 mol%≤X1≤15 mol%
[0034] 2 mol%≤X2≤10 mol%
[0035] 3 mol%≤X3≤25 mol%
[0036] 50 mol%≤X4≤90 mol%
[0037] X1+X2+X3+X4=100 mol%.
[0038] As an improved technical solution of the present application, the biaxially oriented polyester film has a thickness of 12 μm to 188 μm.
[0039] As an improved technical solution of the present application, the biaxially oriented polyester film contains three polyester resin layers A1 / B / A2, wherein the A1 layer accounts for 3% to 29% of the total thickness, and the A2 layer accounts for 3% to 29% of the total thickness.
[0040] As an improved technical solution of the present application, the pure polyester resin is polyethylene terephthalate resin, and the intrinsic viscosity is 0.62 dl / g to 0.68 dl / g.
[0041] As an improved technical solution of the present application, the method for preparing the biaxially oriented polyester film is to mix the functional masterbatch X, the functional masterbatch Y, the functional masterbatch Z and the pure polyester resin with corresponding weight proportions in advance, send them into the corresponding melt extrusion system for extrusion, enter the three-layer co-extrusion die head, and then cast, longitudinally stretch, transversely stretch, heat set, cool, pull and wind up to obtain the film.
[0042] As an improved technical solution of the present application, the melt extrusion temperature is 260°C to 280°C.
[0043] As an improved technical solution of the present application, the longitudinal stretching ratio is 2.7 to 3.8.
[0044] As an improved technical solution of the present application, the transverse stretching ratio is 3.3 to 5.6.
[0045] As an improved technical solution of the present application, the heat setting temperature is 220°C to 243°C.
[0046] The functional masterbatch X, functional masterbatch Y and functional masterbatch Z described in the present invention are named to distinguish different functional masterbatches, the inorganic filler x and inorganic filler y are named to distinguish different types of silica, and the modified dibasic acid contents X1, X2, X3 and X4 are named to distinguish the different amounts of materials used in each step, and the letters themselves have no meaning.
[0047] The beneficial effects achieved by the present invention are embodied in:
[0048] 1. The modified polyester is used in the functional masterbatch to realize the two-in-one functions of the modified polyester and the inorganic particles. If the modified polyester is not used in the functional masterbatch, the functional masterbatch will not have the performance of the modified polyester. The present invention designs the polyester polymer from the microscopic perspective of the polymer chain segment, giving the polyester polymer material new performance and improving the thermal performance and appearance of the product.
[0049] 2. The present invention focuses on theoretical mechanism research and uses a clever combination of crystalline spherical silica particles and crystalline spherical silica particles coated with amorphous silica on the surface, which not only improves the thermal performance of the polyester film, but also ensures the appearance of the film without scratches / scratches on the surface.
[0050] 3. The present invention adopts a combination design of modified polyester and functional masterbatch, and directly melts, extrude and stretches the film, which has simple process and low cost. DETAILED DESCRIPTION
[0051] For ease of understanding of the present invention, the present invention will be described more fully below in conjunction with specific embodiments. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly understood.
[0052] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0053] Definitions: As used herein, dibasic acids are dicarboxylic acids.
[0054] The invention discloses a biaxially oriented polyester film, which comprises three polyester resin layers of A1 / B / A2.
[0055] Among them, the main components of the A1 layer are 10 to 50 parts by weight of functional masterbatch X and 50 to 90 parts by weight of pure polyester resin; the main components of the B layer are 5 to 40 parts by weight of functional masterbatch Y and 60 to 95 parts by weight of pure polyester resin; the main components of the A2 layer are 5 to 30 parts by weight of functional masterbatch Z and 70 to 95 parts by weight of pure polyester resin.
[0056] When the amount of functional masterbatch X added in the A1 layer is less than 10 parts by weight, due to too little addition of inorganic particles in the functional masterbatch, it is difficult to play its role of smoothness and avoiding scratches during winding, and the effect of modified polyester will also be reduced. When the amount of functional masterbatch X added in the A1 layer is greater than 50 parts by weight, too much inorganic particles are added, and the smoothness is excessive, which can easily cause the film to slip when passing through the roller and cause scratches. When the amount of functional masterbatch Y added in the B layer is less than 5 parts by weight, due to the small amount of inorganic particles and modified polyester added, it is difficult to play the role of nucleating agent, and it is also difficult to play the effect of modified polyester to improve the thermal properties of the film; when the amount of functional masterbatch Y added in the B layer is greater than 40 parts by weight, it is easy to cause the film to be brittle as a whole, affecting the machine and deep processing performance, and it will also cause excess performance and waste of functional masterbatch. When the amount of functional masterbatch Z added in the A2 layer is less than 5 parts by weight, the inorganic particles in the functional masterbatch are too little, so it is difficult to play its role of smoothness and avoiding scratches during winding, and the effect of modified polyester will also be reduced; when the amount of functional masterbatch Z added in the A2 layer is greater than 30 parts by weight, too much inorganic particles are added, and the smoothness is excessive, which can easily cause the film to slip when passing through the roller and cause scratches. Due to the different number and material of rollers passed by the A1 side and the A2 side during the production of polyester film, or the selection of downstream deep processing surfaces, there are differences in the amount of functional masterbatch added in the A1 and A2 layers.
[0057] The functional masterbatch X is composed of: 0.3 to 10 parts by weight of inorganic filler x and 90 to 99.7 parts by weight of modified polyester, wherein the inorganic filler x is crystalline spherical silica particles with amorphous silica coated on the surface, the main manufacturer of which is Fuji Silicon Chemical Co., Ltd., and the average particle size is 0.3 μm to 3 μm; the functional masterbatch Z has the same composition as the functional masterbatch X.
[0058] When the amount of inorganic filler x added is less than 0.3 parts by weight, the concentration is too low. To achieve the same effect, a larger proportion of functional masterbatch needs to be added, which can easily cause the viscosity of the surface layer system to differ greatly from that of the core layer, which is not conducive to the overall performance stability and will also increase costs; when the amount of inorganic filler x added is greater than 10 parts by weight, more inorganic particles are added, which can easily cause the viscosity of the masterbatch system to decrease. At the same time, the masterbatch concentration is too high, which is not conducive to adding in a small proportion, and it is easy to produce stratification between the pure polyester resin, making it difficult to ensure the uniformity of the film surface performance. When the average particle size of inorganic filler x is less than 0.3μm, the particle size is too small. When added to the surface layer, it is difficult to exert a smooth effect, resulting in scratches on the film surface; when the average particle size of inorganic filler x is greater than 3μm, the film surface is too rough, which makes it difficult to meet the requirements of IMD, plate glazing and other fields with high requirements for surface smoothness.
[0059] The functional masterbatch Y is composed of 1 to 15 parts by weight of an inorganic filler y and 85 to 99 parts by weight of a modified polyester. The inorganic filler y is crystalline spherical silica particles with an average particle size of 0.03 μm to 1 μm.
[0060] When the amount of inorganic filler y added is less than 1 part by weight, the concentration is too low, the efficiency of masterbatch manufacturing is reduced, and the production cost is increased; when the amount of inorganic filler y added is greater than 15 parts by weight, more inorganic particles are added, which easily causes the viscosity of the masterbatch system to decrease. At the same time, the masterbatch concentration is too high, which is not conducive to small-proportion addition and it is difficult to ensure the uniformity of addition. When the average particle size of inorganic filler y is less than 0.03μm, the smaller the particle size, the higher the surface energy, the easier it is for inorganic particles to agglomerate, generate crystal points, and the difficulty of functional masterbatch manufacturing increases; when the average particle size of inorganic filler y is greater than 1μm, the particle size of inorganic particles is too large, and when added per unit weight, the nucleation sites that can be provided are few, which is not conducive to the formation of crystal nuclei.
[0061] Functional masterbatch Y is used for polyester film B layer, and crystalline spherical silica particles are selected. The main manufacturer is Fuji Silicon Chemical Co., Ltd. This is mainly because the form of a substance determines its performance. Crystalline spherical silica particles have a dense internal structure due to their crystallization. When used as a nucleating agent to participate in the nucleation and crystallization process, compared with ordinary spherical silica particles, when the downstream processing is heated, the crystal system will not be destroyed due to the rupture of the spherical silica particle nucleus, resulting in film deformation. The crystal system formed by crystalline spherical silica particles as a nucleating agent is more stable and temperature-resistant.
[0062] When technicians design a formula to improve the performance of the three-layer polyester film as a whole, they tend to ignore the influence of the surface layer. In fact, as the outermost layer, the surface layer is more easily and first affected by external environmental factors, whether it is heated or stressed. Only when the performance of each layer is improved can the overall performance of the product be improved. Taking this into consideration, the present invention also uses crystalline spherical silica particles as a nucleating agent to improve the heat resistance of the surface layer; however, due to the crystallization of the crystalline spherical silica particles, it has a dense internal structure and the surface hardness of the particles is relatively high. When the polyester film is rolled up, it is easy to cause scratches between layers, affecting the appearance of the product; in addition, long-term operation will also cause wear on the mirror roller surface of the equipment. Therefore, the present invention is cleverly designed by coating the surface of crystalline spherical silica particles with amorphous silica, and the texture of amorphous silica is relatively soft, which not only ensures the improvement of the thermal performance of the film surface, but also avoids the problem of scratches between the film layers and the problem of wear on the mirror roller surface of the equipment.
[0063] The modified polyester adopts 4-(3,5-dicarboxyphenoxy)phthalic acid, 4,4-propanediyldioxydibenzoic acid, 3,5-di(p-carboxyphenyl)benzoic acid and terephthalic acid.
[0064] Among them, the content of 4-(3,5-dicarboxyphenoxy)phthalic acid component relative to the total dicarboxylic acid components in the modified polyester is X1, the content of 4,4-propanediyldioxydibenzoic acid component relative to the total dicarboxylic acid components is X2, the content of 3,5-di(p-carboxyphenyl)benzoic acid component relative to the total dicarboxylic acid components is X3, and the content of terephthalic acid component relative to the total dicarboxylic acid components is X4.
[0065] X1, X2, X3, and X4 satisfy the following relationship:
[0066] 5 mol%≤X1≤15 mol%
[0067] 2 mol%≤X2≤10 mol%
[0068] 3 mol%≤X3≤25 mol%
[0069] 50 mol%≤X4≤90 mol%
[0070] X1+X2+X3+X4=100 mol%.
[0071] Among them, 4-(3,5-dicarboxyphenoxy)phthalic acid has four carboxyl groups and two benzene rings. When the carboxyl groups on the two benzene rings participate in the reaction respectively, the two benzene rings directly participate in the formation of the polymer segment, which improves the rigidity of the polymer segment; when the carboxyl groups on the same benzene ring participate in the reaction, one of the benzene rings is located in the side chain, which increases the steric hindrance of the polymer segment and helps to maintain the stability of the segment. 4,4-propanediyldioxydibenzoic acid and 3,5-di(p-carboxyphenyl)benzoic acid also have two benzene rings participating in the formation of the polymer segment, which improves the overall rigidity of the polymer segment. In addition, when the two benzene rings of 3,5-di(p-carboxyphenyl)benzoic acid participate in the reaction, there is also a benzene ring located in the side chain, which increases the steric hindrance of the polymer segment and maintains the stability of the segment. In the direction of the polymer segment, it is connected by chemical bonds and is relatively stable. Perpendicular to the direction of the polymer chain, a strong hydrogen bond can be formed between the carboxyl group and the phenoxy group, which plays a role in fixing the molecular chains and ensuring that the film does not deform during the subsequent heating process. At the same time, when the phenoxy group is located in the polymer chain, its special structure can provide a buffer for the movement of the polymer chain, which is beneficial to improving the micro deformation in the subsequent processing process.
[0072] 4-(3,5-dicarboxyphenoxy)phthalic acid, 4,4-propanediyldioxydibenzoic acid, 3,5-di(p-carboxyphenyl)benzoic acid, and terephthalic acid can achieve the best technical effect through the design of the appropriate total dicarboxylic acid component content in the present invention. When the modified polyester is used for the surface layer, the scratch resistance of the polyester film surface is also correspondingly improved. Since the inorganic particles have limited effect on improving the thermal properties of the film, the combined design of the modified polyester and the inorganic particles of the present invention can make the relevant properties of the functional masterbatch more fully exerted.
[0073] The modified polyester, functional masterbatch X and functional masterbatch Y of the present invention can be prepared by the following method:
[0074] The preparation method of modified polyester is as follows:
[0075] 1. Add the required dibasic acid, diol, catalyst and stabilizer into the polyester reactor in sequence, beat for 15 minutes, and introduce nitrogen protection, and esterify for 2h to 3.5h at 235℃~260℃ and 260KPa. The dibasic acid is selected from 4-(3,5-dicarboxyphenoxy)phthalic acid, 4,4-propanediyldioxydibenzoic acid, 3,5-di(p-carboxyphenyl)benzoic acid and terephthalic acid, wherein the content of 4-(3,5-dicarboxyphenoxy)phthalic acid component relative to the total dicarboxylic acid components in the modified polyester is 5 mol%≤X1≤15 mol%; the content of 4,4-propanediyldioxydibenzoic acid component relative to the total dicarboxylic acid components is 2 mol%≤X2≤10 mol%; the content of 3,5-di(p-carboxyphenyl)benzoic acid component relative to the total dicarboxylic acid components is 3 mol%≤X3≤25 mol%; the content of terephthalic acid component relative to the total dicarboxylic acid components is 50 mol%≤X4≤90 mol%, and X1+X2+X3+X4=100 mol%.
[0076] The diol is selected from ethylene glycol, propylene glycol, butanediol, 1,4-cyclohexanedimethanol, hexanediol, polyethylene oxide glycol, etc., preferably ethylene glycol; the molar ratio of the dibasic acid to the diol is 1:1.23 to 1:1.43; the catalyst is selected from antimony, iron, aluminum, germanium, titanium, etc., preferably ethylene glycol antimony, and the addition amount is 80ppm to 300ppm; the stabilizer is selected from trimethyl phosphate, triethyl phosphate, triphenyl phosphate, tri-n-butyl phosphate, tetrabutyl titanate, tetraethyl titanate, etc., preferably triphenyl phosphate, and the addition amount is 30ppm to 100ppm.
[0077] 2. The end point of esterification is determined according to the amount of water output. After the esterification is complete, vacuum is turned on. The polycondensation reaction is carried out for 3h to 5h at 262°C to 280°C and 20Pa to 65Pa. After spinning, cooling, pelletizing and drying, the modified polyester of the present invention is obtained. The modified polyester has an intrinsic viscosity of 0.60dl / g to 0.69dl / g.
[0078] The preparation method of functional masterbatch Y is:
[0079] The modified polyester prepared above with an intrinsic viscosity of 0.60dl / g to 0.69dl / g is selected as the base material, and then 85 to 99 parts by weight of the modified polyester and 1 to 15 parts by weight of crystalline spherical silica particles (inorganic filler y) with an average particle size of 0.03μm to 1μm are mixed evenly; they are sent to a twin-screw extruder, vacuumed, and made into silk, cooled, pelletized, and dried to obtain the functional masterbatch Y of the present invention, and the functional masterbatch Y has an intrinsic viscosity of 0.56dl / g to 0.66dl / g. The present invention uses a twin-screw in-and-out granulation method instead of a synthetic method. The main reason is that when the synthetic method is used, the long-term high temperature during the esterification and polycondensation process may destroy the surface coating structure of the inorganic particles and affect its effect. The same method as the functional masterbatch Y can be used to prepare the functional masterbatch X / functional masterbatch Z with an intrinsic viscosity of 0.58dl / g to 0.68dl / g.
[0080] The biaxially oriented polyester film has a thickness of 12 μm to 188 μm.
[0081] The biaxially oriented polyester film contains three polyester resin layers, A1 / B / A2, wherein the A1 layer accounts for 3% to 29% of the total thickness, and the A2 layer accounts for 3% to 29% of the total thickness.
[0082] The biaxially oriented polyester film comprises three polyester resin layers, A1 / B / A2, and the thickness of the A1 layer and the thickness of the A2 layer may be the same or different.
[0083] The pure polyester resin is polyethylene terephthalate resin, and the intrinsic viscosity is 0.62 dl / g to 0.68 dl / g.
[0084] The biaxially oriented polyester film of the present invention can be prepared by the following method:
[0085] 1. The functional masterbatch X, the functional masterbatch Y, the functional masterbatch Z and the pure polyester resin with corresponding weight fractions are mixed in advance and sent into the corresponding melt extrusion system for extrusion.
[0086] 2. The melt is co-extruded through the die head and cast onto the casting roll to form a three-layer co-extruded casting sheet.
[0087] 3. The cast sheet is longitudinally stretched with a longitudinal stretching ratio of 2.7 to 3.8.
[0088] 4. The longitudinally drawn sheet is stretched transversely with a transverse stretching ratio of 3.3 to 5.6.
[0089] 5. The stretched film is heat-set at a temperature of 220°C to 243°C.
[0090] 6. Then cool, pull and reel.
[0091] It should be noted that, without affecting the technical effect of the present invention, the polyester film of the present invention can be subjected to corona pretreatment on one or both sides, or primer pretreatment with a thickness of 0.01 μm to 0.20 μm, and then supplied to downstream for further processing.
[0092] The present invention is further described below in conjunction with embodiments, but the implementation and protection scope of the present invention are not limited to these embodiments.
[0093] Example 1
[0094] Preparation of modified polyester:
[0095] According to the molar ratio of dibasic acid to ethylene glycol of 1:1.23, the addition amount of ethylene glycol antimony is 80ppm, and the addition amount of triphenyl phosphate is 30ppm. Among them, the content of 4-(3,5-dicarboxyphenoxy)phthalic acid, 4,4-propanediyldioxydibenzoic acid, 3,5-di(p-carboxyphenyl)benzoic acid, and terephthalic acid in the dibasic acid relative to the total dicarboxylic acid components is: X1=5mol%, X2=2mol%, X3=1mol%, X4=1mol%, X5=1mol%, X6=1mol%, X7=1mol%, X8=1mol%, X9=1mol%, X10=1mol%, X110=1mol%, X120=1mol%, X130=1mol%, X140=1mol%, X150=1mol%, X160=1mol%, X170=1mol%, X180=1mol%, X190=1mol%, X210=1mol%, X220=1mol%, X23 ... =3 mol%, X4 = 90 mol%, after the above are evenly mixed, added into a polyester synthesis reactor, pulped for 15 minutes, and nitrogen protection is introduced, and esterification is carried out at 236°C ~ 262°C, 265KPa for 2h; after the esterification is completed, vacuum is turned on, and the polycondensation reaction is carried out at 265°C ~ 282°C, 20Pa for 3h, and after silk making, cooling, pelletizing and drying, a modified polyester with a characteristic viscosity of 0.60dl / g is obtained.
[0096] Functional masterbatch Y preparation:
[0097] 85 parts by weight of the modified polyester with a characteristic viscosity of 0.60 dl / g prepared above and 15 parts by weight of crystalline spherical silica particles (inorganic filler y) with an average particle size of 0.03 μm are mixed evenly and fed into a twin-screw extruder together; the vacuum is turned on, and the functional masterbatch Y with a characteristic viscosity of 0.56 dl / g is obtained through filament making, cooling, pelletizing and drying.
[0098] Functional masterbatch X / functional masterbatch Z preparation:
[0099] 90 parts by weight of the modified polyester with an intrinsic viscosity of 0.60 dl / g prepared above and 10 parts by weight of crystalline spherical silica particles with an average particle size of 0.3 μm and amorphous silica coated on the surface (inorganic filler x) were mixed uniformly; they were fed into a twin-screw extruder, vacuumed, and subjected to filament making, cooling, pelletizing, and drying to obtain a functional masterbatch X with an intrinsic viscosity of 0.58 dl / g. The functional masterbatch Z had the same composition as the functional masterbatch X.
[0100] 10 parts by weight of functional masterbatch X with an intrinsic viscosity of 0.58 dl / g and 90 parts by weight of pure polyester resin with an intrinsic viscosity of 0.62 dl / g (A1 layer), 5 parts by weight of functional masterbatch Y with an intrinsic viscosity of 0.56 dl / g and 95 parts by weight of pure polyester resin with an intrinsic viscosity of 0.62 dl / g (B layer), 5 parts by weight of functional masterbatch Z with an intrinsic viscosity of 0.58 dl / g and 95 parts by weight of pure polyester resin with an intrinsic viscosity of 0.62 dl / g (A2 layer) were mixed in advance and sent to a corresponding melt extrusion system for extrusion at a temperature of 260°C. The film is melt-extruded, enters a three-layer die for co-extrusion, and is cast onto a casting roll to form an A1 / B / A2 structure extruded casting film; the casting film is longitudinally stretched, the longitudinal stretching temperature is 75°C to 87°C, and the longitudinal stretching ratio is 3.8; the longitudinally stretched film is transversely stretched, the transverse stretching temperature is 108°C to 130°C, and the transverse stretching ratio is 5.6; the stretched film is shaped and cooled, and the shaping temperature is 220°C; the film is then cooled, pulled, and rolled to obtain a biaxially oriented polyester film with a thickness of 12 μm, wherein the A1 layer accounts for 29% of the total thickness, and the A2 layer accounts for 29% of the total thickness.
[0101] Example 2
[0102] Preparation of modified polyester:
[0103] According to the molar ratio of dibasic acid to ethylene glycol of 1:1.3, the addition amount of ethylene glycol antimony is 90ppm, and the addition amount of triphenyl phosphate is 35ppm. Among them, the content of 4-(3,5-dicarboxyphenoxy)phthalic acid, 4,4-propanediyldioxydibenzoic acid, 3,5-di(p-carboxyphenyl)benzoic acid, and terephthalic acid in the dibasic acid relative to the total dicarboxylic acid components is: X1=5mol%, X2=3mol%, X3=1mol%, =5 mol%, X4=87 mol%, after the above are evenly mixed, added into a polyester synthesis reactor, beaten for 15 minutes, and nitrogen protection is introduced, and esterification is carried out at 236°C~262°C, 265KPa for 2h; after the esterification is completed, vacuum is turned on, and condensation reaction is carried out at 265°C~282°C, 30Pa for 3h, and after silk making, cooling, pelletizing and drying, a modified polyester with a characteristic viscosity of 0.61dl / g is obtained.
[0104] Functional masterbatch Y preparation:
[0105] 87 parts by weight of the modified polyester with a characteristic viscosity of 0.61 dl / g prepared above and 13 parts by weight of crystalline spherical silica particles (inorganic filler y) with an average particle size of 0.03 μm were mixed evenly and fed into a twin-screw extruder together. The vacuum was turned on, and the functional masterbatch Y with a characteristic viscosity of 0.58 dl / g was obtained through filament making, cooling, pelletizing and drying.
[0106] Functional masterbatch X / functional masterbatch Z preparation:
[0107] 93 parts by weight of the modified polyester with an intrinsic viscosity of 0.61 dl / g prepared above and 7 parts by weight of crystalline spherical silica particles with an average particle size of 0.5 μm and amorphous silica coated on the surface (inorganic filler x) were mixed evenly and fed into a twin-screw extruder together. The mixture was vacuumed and subjected to filament making, cooling, pelletizing and drying to obtain a functional masterbatch X with an intrinsic viscosity of 0.59 dl / g. The functional masterbatch Z had the same composition as the functional masterbatch X.
[0108] 15 parts by weight of functional masterbatch X with an intrinsic viscosity of 0.59 dl / g and 85 parts by weight of pure polyester resin with an intrinsic viscosity of 0.63 dl / g (A1 layer), 8 parts by weight of functional masterbatch Y with an intrinsic viscosity of 0.58 dl / g and 92 parts by weight of pure polyester resin with an intrinsic viscosity of 0.63 dl / g (B layer), 10 parts by weight of functional masterbatch Z with an intrinsic viscosity of 0.59 dl / g and 90 parts by weight of pure polyester resin with an intrinsic viscosity of 0.63 dl / g (A2 layer) were mixed in advance and sent to the corresponding melt extrusion system for extrusion at a temperature of 265°C. The film is melt extruded, enters a three-layer die for co-extrusion, and is cast onto a casting roll to form an A1 / B / A2 structure extruded casting film; the casting film is longitudinally stretched at a temperature of 75°C to 87°C and a longitudinal stretch ratio of 3.6; the longitudinally stretched film is transversely stretched at a temperature of 108°C to 130°C and a transverse stretch ratio of 5.5; the stretched film is shaped and cooled at a shaping temperature of 225°C; the film is then cooled, pulled, and rolled to obtain a biaxially oriented polyester film with a thickness of 19 μm, wherein the A1 layer accounts for 27% of the total thickness and the A2 layer accounts for 27% of the total thickness.
[0109] Example 3
[0110] Preparation of modified polyester:
[0111] According to the molar ratio of dibasic acid to ethylene glycol of 1:1.28, the addition amount of ethylene glycol antimony is 150ppm, and the addition amount of triphenyl phosphate is 60ppm. Among them, the content rate of each component of 4-(3,5-dicarboxyphenoxy)phthalic acid, 4,4-propanediyldioxydibenzoic acid, 3,5-di(p-carboxyphenyl)benzoic acid, and terephthalic acid in the dibasic acid relative to the total dicarboxylic acid component is: X1=7 mol%, X2=5 mol%, X3= 8 mol%, X4 = 80 mol%, after the above are evenly mixed; added to a polyester synthesis reactor, pulping for 15 minutes, and nitrogen protection, esterification for 2.5 hours at 236°C ~ 262°C, 265KPa; after the esterification is completed, vacuumization is turned on, and condensation reaction is carried out at 265°C ~ 282°C, 30Pa for 3.5 hours. After silk making, cooling, pelletizing and drying, a modified polyester with a characteristic viscosity of 0.63dl / g is obtained.
[0112] Functional masterbatch Y preparation:
[0113] 90 parts by weight of the modified polyester with a characteristic viscosity of 0.63 dl / g prepared above and 10 parts by weight of crystalline spherical silica particles (inorganic filler y) with an average particle size of 0.05 μm are mixed evenly and fed into a twin-screw extruder together. The vacuum is turned on, and the functional masterbatch Y with a characteristic viscosity of 0.60 dl / g is obtained through filament making, cooling, pelletizing and drying.
[0114] Functional masterbatch X / functional masterbatch Z preparation:
[0115] 95 parts by weight of the modified polyester with an intrinsic viscosity of 0.63 dl / g prepared above and 5 parts by weight of crystalline spherical silica particles with an average particle size of 0.5 μm and amorphous silica coated on the surface (inorganic filler x) were mixed evenly and fed into a twin-screw extruder together. The mixture was vacuumed and subjected to filament making, cooling, pelletizing and drying to obtain a functional masterbatch X with an intrinsic viscosity of 0.60 dl / g. The functional masterbatch Z had the same composition as the functional masterbatch X.
[0116] 18 parts by weight of functional masterbatch X with an intrinsic viscosity of 0.60 dl / g and 82 parts by weight of pure polyester resin with an intrinsic viscosity of 0.63 dl / g (A1 layer), 10 parts by weight of functional masterbatch Y with an intrinsic viscosity of 0.60 dl / g and 90 parts by weight of pure polyester resin with an intrinsic viscosity of 0.63 dl / g (B layer), 18 parts by weight of functional masterbatch Z with an intrinsic viscosity of 0.60 dl / g and 82 parts by weight of pure polyester resin with an intrinsic viscosity of 0.63 dl / g (A2 layer) were mixed in advance and sent to the corresponding melt extrusion system for extrusion at a temperature of 270°C. The film is melt extruded, enters a three-layer die for co-extrusion, and is cast onto a casting roll to form an A1 / B / A2 structure extruded casting film; the casting film is longitudinally stretched at a temperature of 75°C to 87°C and a longitudinal stretch ratio of 3.5; the longitudinally stretched film is transversely stretched at a temperature of 108°C to 130°C and a transverse stretch ratio of 5.1; the stretched film is shaped and cooled at a shaping temperature of 230°C; the film is then cooled, pulled, and rolled to obtain a biaxially oriented polyester film with a thickness of 23 μm, wherein the A1 layer accounts for 25% of the total thickness and the A2 layer accounts for 20% of the total thickness.
[0117] Example 4
[0118] Preparation of modified polyester:
[0119] According to the molar ratio of dibasic acid to ethylene glycol of 1:1.33, the addition amount of ethylene glycol antimony is 180ppm, and the addition amount of triphenyl phosphate is 70ppm. Among them, the content of 4-(3,5-dicarboxyphenoxy)phthalic acid, 4,4-propanediyldioxydibenzoic acid, 3,5-di(p-carboxyphenyl)benzoic acid, and terephthalic acid in the dibasic acid relative to the total dicarboxylic acid components is: X1=10mol%, X2=7mol%, X3=10mol%, X4=10mol%, X5=10mol%, X6=10mol%, X7=10mol%, X8=10mol%, X9=10mol%, X10=10mol%, X11=10mol%, X12=10mol%, X13=10mol%, X14=10mol%, X15=10mol%, X16=10mol%, X17=10mol%, X18=10mol%, X19=10mol%, X20=10mol%, X21=10mol%, X22=10mol%, X3 =12 mol%, X4=71 mol%, after the above are evenly mixed, added into a polyester synthesis reactor, beaten for 15 minutes, and nitrogen protection is introduced, and esterification is carried out at 236°C~262°C, 265KPa for 3h; after the esterification is completed, vacuum is turned on, and the polycondensation reaction is carried out at 265°C~282°C, 35Pa for 3.5h, and after silk making, cooling, pelletizing and drying, a modified polyester with a characteristic viscosity of 0.65dl / g is obtained.
[0120] Functional masterbatch Y preparation:
[0121] 92 parts by weight of the modified polyester with a characteristic viscosity of 0.65 dl / g prepared above and 8 parts by weight of crystalline spherical silica particles (inorganic filler y) with an average particle size of 0.1 μm were mixed evenly and fed into a twin-screw extruder together. The vacuum was turned on, and the functional masterbatch Y with a characteristic viscosity of 0.62 dl / g was obtained through filament making, cooling, pelletizing and drying.
[0122] Functional masterbatch X / functional masterbatch Z preparation:
[0123] 94 parts by weight of the modified polyester with an intrinsic viscosity of 0.65 dl / g prepared above and 6 parts by weight of crystalline spherical silica particles with an average particle size of 1 μm and amorphous silica coated on the surface (inorganic filler x) were mixed uniformly; they were fed into a twin-screw extruder together, and vacuum was turned on. After filament making, cooling, pelletizing and drying, a functional masterbatch X with an intrinsic viscosity of 0.63 dl / g was obtained. The functional masterbatch Z had the same composition as the functional masterbatch X.
[0124] 20 parts by weight of functional masterbatch X with an intrinsic viscosity of 0.63 dl / g and 80 parts by weight of pure polyester resin with an intrinsic viscosity of 0.64 dl / g (A1 layer), 15 parts by weight of functional masterbatch Y with an intrinsic viscosity of 0.62 dl / g and 85 parts by weight of pure polyester resin with an intrinsic viscosity of 0.64 dl / g (B layer), 18 parts by weight of functional masterbatch Z with an intrinsic viscosity of 0.63 dl / g and 82 parts by weight of pure polyester resin with an intrinsic viscosity of 0.64 dl / g (A2 layer) were mixed in advance and sent to the corresponding melt extrusion system for extrusion at a temperature of 270°C. The film is melt extruded, enters a three-layer die for co-extrusion, and is cast onto a casting roll to form an A1 / B / A2 structure extruded casting film; the casting film is longitudinally stretched at a temperature of 75°C to 87°C and a longitudinal stretch ratio of 3.4; the longitudinally stretched film is transversely stretched at a temperature of 108°C to 130°C and a transverse stretch ratio of 4.9; the stretched film is shaped and cooled at a shaping temperature of 230°C; the film is then cooled, pulled, and rolled to obtain a biaxially oriented polyester film with a thickness of 30 μm, wherein the A1 layer accounts for 18% of the total thickness and the A2 layer accounts for 18% of the total thickness.
[0125] Example 5
[0126] Preparation of modified polyester:
[0127] According to the molar ratio of dibasic acid to ethylene glycol of 1:1.35, the addition amount of ethylene glycol antimony is 180ppm, and the addition amount of triphenyl phosphate is 80ppm. Among them, the content of 4-(3,5-dicarboxyphenoxy)phthalic acid, 4,4-propanediyldioxydibenzoic acid, 3,5-di(p-carboxyphenyl)benzoic acid, and terephthalic acid in the dibasic acid relative to the total dicarboxylic acid components is: X1=9 mol%, X2=6 mol%, X3=10 mol%, X4=10 mol%, X5=10 mol%, X6=10 mol%, X7=10 mol%, X8=10 mol%, X9=10 mol%, X11=10 mol%, X12=10 mol%, X13=10 mol%, X14=10 mol%, X15=10 mol%, X16=10 mol%, X17=10 mol%, X18=10 mol%, X19=10 mol%, X20=10 mol%, X218=10 mol%, X22 =20 mol%, X4=65 mol%, after the above are evenly mixed, added into a polyester synthesis reactor, beaten for 15 minutes, and nitrogen protection is introduced, and esterification is carried out at 236°C~262°C, 265KPa for 3h; after the esterification is completed, vacuum is turned on, and condensation reaction is carried out at 265°C~282°C, 40Pa for 4h, and after silk making, cooling, pelletizing and drying, a modified polyester with a characteristic viscosity of 0.65dl / g is obtained.
[0128] Functional masterbatch Y preparation:
[0129] 93 parts by weight of the modified polyester with a characteristic viscosity of 0.65 dl / g prepared above and 7 parts by weight of crystalline spherical silica particles (inorganic filler y) with an average particle size of 0.3 μm were mixed evenly and fed into a twin-screw extruder together. The vacuum was turned on, and the functional masterbatch Y with a characteristic viscosity of 0.62 dl / g was obtained through filament making, cooling, pelletizing and drying.
[0130] Functional masterbatch X / functional masterbatch Z preparation:
[0131] 96.5 parts by weight of the modified polyester with an intrinsic viscosity of 0.65 dl / g prepared above and 3.5 parts by weight of crystalline spherical silica particles with an average particle size of 1.5 μm and amorphous silica coated on the surface (inorganic filler x) were mixed evenly and fed into a twin-screw extruder together. The mixture was vacuumed and subjected to filament making, cooling, pelletizing and drying to obtain a functional masterbatch X with an intrinsic viscosity of 0.64 dl / g. The functional masterbatch Z had the same composition as the functional masterbatch X.
[0132] 25 parts by weight of functional masterbatch X with an intrinsic viscosity of 0.64 dl / g and 75 parts by weight of pure polyester resin with an intrinsic viscosity of 0.65 dl / g (A1 layer), 20 parts by weight of functional masterbatch Y with an intrinsic viscosity of 0.62 dl / g and 80 parts by weight of pure polyester resin with an intrinsic viscosity of 0.65 dl / g (B layer), 15 parts by weight of functional masterbatch Z with an intrinsic viscosity of 0.64 dl / g and 85 parts by weight of pure polyester resin with an intrinsic viscosity of 0.65 dl / g (A2 layer) were mixed in advance and sent to the corresponding melt extrusion system for extrusion at a temperature of 275°C. The film is melt extruded, enters a three-layer die for co-extrusion, and is cast onto a casting roll to form an A1 / B / A2 structure extruded casting film; the casting film is longitudinally stretched at a temperature of 75°C to 87°C and a longitudinal stretch ratio of 3.3; the longitudinally stretched film is transversely stretched at a temperature of 108°C to 130°C and a transverse stretch ratio of 4.8; the stretched film is shaped and cooled at a temperature of 230°C; the film is then cooled, pulled, and rolled to obtain a biaxially oriented polyester film with a thickness of 50 μm, wherein the A1 layer accounts for 16% of the total thickness and the A2 layer accounts for 16% of the total thickness.
[0133] Example 6
[0134] Preparation of modified polyester:
[0135] According to the molar ratio of dibasic acid to ethylene glycol of 1:1.4, the addition amount of ethylene glycol antimony is 200ppm, and the addition amount of triphenyl phosphate is 80ppm. Among them, the content rate of each component of the dibasic acid relative to the total dicarboxylic acid component is: X1=12mol%, X2=8mol%, X3= 18 mol%, X4 = 62 mol%, after the above are evenly mixed, added into a polyester synthesis reactor, beaten for 15 minutes, and nitrogen protection is introduced, and esterification is carried out at 236°C ~ 262°C, 265KPa for 2.5 hours; after the esterification is completed, vacuumization is turned on, and condensation reaction is carried out at 265°C ~ 282°C, 40Pa for 4 hours. After silk making, cooling, pelletizing and drying, a modified polyester with a characteristic viscosity of 0.65dl / g is obtained.
[0136] Functional masterbatch Y preparation:
[0137] 95 parts by weight of the modified polyester with a characteristic viscosity of 0.65 dl / g prepared above and 5 parts by weight of crystalline spherical silica particles (inorganic filler y) with an average particle size of 0.5 μm were mixed evenly and fed into a twin-screw extruder together. The vacuum was turned on, and the functional masterbatch Y with a characteristic viscosity of 0.63 dl / g was obtained through filament making, cooling, pelletizing and drying.
[0138] Functional masterbatch X / functional masterbatch Z preparation:
[0139] 97 parts by weight of the modified polyester with an intrinsic viscosity of 0.65 dl / g prepared above and 3 parts by weight of crystalline spherical silica particles with an average particle size of 1.8 μm and amorphous silica coated on the surface (inorganic filler x) were mixed evenly and fed into a twin-screw extruder together. The mixture was vacuumed and subjected to filament making, cooling, pelletizing and drying to obtain a functional masterbatch X with an intrinsic viscosity of 0.63 dl / g. The functional masterbatch Z had the same composition as the functional masterbatch X.
[0140] 27 parts by weight of functional masterbatch X with an intrinsic viscosity of 0.63 dl / g and 73 parts by weight of pure polyester resin with an intrinsic viscosity of 0.65 dl / g (A1 layer), 22 parts by weight of functional masterbatch Y with an intrinsic viscosity of 0.63 dl / g and 78 parts by weight of pure polyester resin with an intrinsic viscosity of 0.65 dl / g (B layer), 18 parts by weight of functional masterbatch Z with an intrinsic viscosity of 0.63 dl / g and 82 parts by weight of pure polyester resin with an intrinsic viscosity of 0.65 dl / g (A2 layer) were mixed in advance and sent to the corresponding melt extrusion system for extrusion at a temperature of 275°C. The film is melt extruded, enters a three-layer die for co-extrusion, and is cast onto a casting roll to form an A1 / B / A2 structure extruded casting film; the casting film is longitudinally stretched at a temperature of 75°C to 87°C and a longitudinal stretch ratio of 3.3; the longitudinally stretched film is transversely stretched at a temperature of 108°C to 130°C and a transverse stretch ratio of 4.8; the stretched film is shaped and cooled at a shaping temperature of 230°C; the film is then cooled, pulled, and rolled to obtain a biaxially oriented polyester film with a thickness of 75 μm, wherein the A1 layer accounts for 16% of the total thickness and the A2 layer accounts for 16% of the total thickness.
[0141] Example 7
[0142] Preparation of modified polyester:
[0143] According to the molar ratio of dibasic acid to ethylene glycol of 1:1.4, the addition amount of ethylene glycol antimony is 250ppm, and the addition amount of triphenyl phosphate is 90ppm. Among them, the content of 4-(3,5-dicarboxyphenoxy)phthalic acid, 4,4-propanediyldioxydibenzoic acid, 3,5-di(p-carboxyphenyl)benzoic acid, and terephthalic acid in the dibasic acid relative to the total dicarboxylic acid components is: X1=13 mol%, X2=8 mol%, X3=10 mol%, X4=10 mol%, X5=10 mol%, X6=10 mol%, X7=10 mol%, X8=10 mol%, X9=10 mol%, X10=10 mol%, X11=10 mol%, X12=10 mol%, X13=10 mol%, X14=10 mol%, X15=10 mol%, X16=10 mol%, X17=10 mol%, X18=10 mol%, X19=10 mol%, X20=10 mol%, X218=10 mol%, X228=10 mol%, X23 =20 mol%, X4=59 mol%, after the above are evenly mixed, added into a polyester synthesis reactor, beaten for 15 minutes, and nitrogen protection is introduced, and esterification is carried out at 236°C ~ 262°C, 265KPa for 3h; after the esterification is completed, vacuum is turned on, and condensation reaction is carried out at 265°C ~ 282°C, 50Pa for 4h, and after silk making, cooling, pelletizing and drying, a modified polyester with a characteristic viscosity of 0.66dl / g is obtained.
[0144] Functional masterbatch Y preparation:
[0145] 96 parts by weight of the modified polyester with a characteristic viscosity of 0.66 dl / g prepared above and 4 parts by weight of crystalline spherical silica particles (inorganic filler y) with an average particle size of 0.8 μm were mixed evenly and fed into a twin-screw extruder together. The vacuum was turned on, and the functional masterbatch Y with a characteristic viscosity of 0.64 dl / g was obtained through filament making, cooling, pelletizing and drying.
[0146] Functional masterbatch X / functional masterbatch Z preparation:
[0147] 96 parts by weight of the modified polyester with an intrinsic viscosity of 0.66 dl / g prepared above and 4 parts by weight of crystalline spherical silica particles with an average particle size of 2 μm and amorphous silica coated on the surface (inorganic filler x) were mixed evenly and fed into a twin-screw extruder together. The mixture was vacuumed and subjected to filament making, cooling, pelletizing and drying to obtain a functional masterbatch X with an intrinsic viscosity of 0.64 dl / g. The functional masterbatch Z had the same composition as the functional masterbatch X.
[0148] 30 parts by weight of functional masterbatch X with an intrinsic viscosity of 0.64 dl / g and 70 parts by weight of pure polyester resin with an intrinsic viscosity of 0.66 dl / g (A1 layer), 25 parts by weight of functional masterbatch Y with an intrinsic viscosity of 0.64 dl / g and 75 parts by weight of pure polyester resin with an intrinsic viscosity of 0.66 dl / g (B layer), 20 parts by weight of functional masterbatch Z with an intrinsic viscosity of 0.64 dl / g and 80 parts by weight of pure polyester resin with an intrinsic viscosity of 0.66 dl / g (A2 layer) were mixed in advance and sent to the corresponding melt extrusion system for extrusion at a temperature of 275°C. The film is melt extruded, enters a three-layer die for co-extrusion, and is cast onto a casting roll to form an A1 / B / A2 structure extruded casting film; the casting film is longitudinally stretched at a temperature of 75°C to 87°C and a longitudinal stretch ratio of 3.2; the longitudinally stretched film is transversely stretched at a temperature of 108°C to 130°C and a transverse stretch ratio of 4.6; the stretched film is shaped and cooled at a shaping temperature of 235°C; the film is then cooled, pulled, and rolled to obtain a biaxially oriented polyester film with a thickness of 100 μm, wherein the A1 layer accounts for 15% of the total thickness and the A2 layer accounts for 15% of the total thickness.
[0149] Example 8
[0150] Preparation of modified polyester:
[0151] According to the molar ratio of dibasic acid to ethylene glycol of 1:1.43, the addition amount of ethylene glycol antimony is 300ppm, and the addition amount of triphenyl phosphate is 100ppm. Among them, the content rate of each component of the dibasic acid relative to the total dicarboxylic acid component is: X1=15mol%, X2=10mol%, X 3=25 mol %, X4=50 mol %, after the above are evenly mixed, added into a polyester synthesis reactor, beaten for 15 minutes, and nitrogen protection is introduced, and esterification is carried out at 236℃~262℃, 265KPa for 3.5h; after the esterification is completed, vacuumization is turned on, and condensation reaction is carried out at 265℃~282℃, 65Pa for 5h, and after silk making, cooling, pelletizing and drying, a modified polyester with a characteristic viscosity of 0.69dl / g is obtained.
[0152] Functional masterbatch Y preparation:
[0153] 99 parts by weight of the modified polyester with a characteristic viscosity of 0.69 dl / g prepared above and 1 part by weight of crystalline spherical silica particles with an average particle size of 1 μm (inorganic filler y) are mixed evenly and fed into a twin-screw extruder together. The vacuum is turned on, and the functional masterbatch Y with a characteristic viscosity of 0.66 dl / g is obtained through filament making, cooling, pelletizing and drying.
[0154] Functional masterbatch X / functional masterbatch Z preparation:
[0155] 99.7 parts by weight of the modified polyester with an intrinsic viscosity of 0.69 dl / g prepared above and 0.3 parts by weight of crystalline spherical silica particles with an average particle size of 3 μm and amorphous silica coated on the surface (inorganic filler x) were mixed uniformly; they were fed into a twin-screw extruder, vacuumed, and subjected to filament making, cooling, pelletizing, and drying to obtain a functional masterbatch X with an intrinsic viscosity of 0.68 dl / g. The functional masterbatch Z had the same composition as the functional masterbatch X.
[0156] 50 parts by weight of functional masterbatch X with an intrinsic viscosity of 0.68 dl / g and 50 parts by weight of pure polyester resin with an intrinsic viscosity of 0.68 dl / g (A1 layer), 40 parts by weight of functional masterbatch Y with an intrinsic viscosity of 0.66 dl / g and 60 parts by weight of pure polyester resin with an intrinsic viscosity of 0.68 dl / g (B layer), 30 parts by weight of functional masterbatch Z with an intrinsic viscosity of 0.68 dl / g and 70 parts by weight of pure polyester resin with an intrinsic viscosity of 0.68 dl / g (A2 layer) were mixed in advance and sent to the corresponding melt extrusion system for extrusion at a temperature of 280°C. The film is melt extruded, enters a three-layer die for co-extrusion, and is cast onto a casting roll to form an A1 / B / A2 structure extruded casting film; the casting film is longitudinally stretched at a temperature of 75°C to 87°C and a longitudinal stretch ratio of 3.2; the longitudinally stretched film is transversely stretched at a temperature of 108°C to 130°C and a transverse stretch ratio of 4.4; the stretched film is shaped and cooled at a shaping temperature of 235°C; the film is then cooled, pulled, and rolled to obtain a biaxially oriented polyester film with a thickness of 125 μm, wherein the A1 layer accounts for 10% of the total thickness and the A2 layer accounts for 10% of the total thickness.
[0157] Example 9
[0158] Preparation of modified polyester:
[0159] According to the molar ratio of dibasic acid to ethylene glycol of 1:1.38, the addition amount of ethylene glycol antimony is 200ppm, and the addition amount of triphenyl phosphate is 90ppm. Among them, the content of 4-(3,5-dicarboxyphenoxy)phthalic acid, 4,4-propanediyldioxydibenzoic acid, 3,5-di(p-carboxyphenyl)benzoic acid, and terephthalic acid in the dibasic acid relative to the total dicarboxylic acid components is: X1=15mol%, X2=9mol%, X3=10mol%, X4=10mol%, X5=10mol%, X6=10mol%, X7=10mol%, X8=10mol%, X9=10mol%, X10=10mol%, X11=10mol%, X12=10mol%, X13=10mol%, X14=10mol%, X15=10mol%, X16=10mol%, X17=10mol%, X18=10mol%, X19=10mol%, X20=10mol%, X219=10mol%, X22 =15 mol%, X4=61 mol%, after the above are evenly mixed, added into a polyester synthesis reactor, beaten for 15 minutes, and nitrogen protection is introduced, and esterification is carried out at 236°C~262°C, 265KPa for 2.5 hours; after the esterification is completed, vacuumization is turned on, and condensation reaction is carried out at 265°C~282°C, 50Pa for 4 hours. After silk making, cooling, pelletizing and drying, a modified polyester with a characteristic viscosity of 0.66dl / g is obtained.
[0160] Functional masterbatch Y preparation:
[0161] 98.5 parts by weight of the modified polyester with a characteristic viscosity of 0.66 dl / g prepared above and 1.5 parts by weight of crystalline spherical silica particles (inorganic filler y) with an average particle size of 0.6 μm were mixed evenly and fed into a twin-screw extruder together. The vacuum was turned on, and the functional masterbatch Y with a characteristic viscosity of 0.62 dl / g was obtained through filament making, cooling, pelletizing and drying.
[0162] Functional masterbatch X / functional masterbatch Z preparation:
[0163] 99 parts by weight of the modified polyester with an intrinsic viscosity of 0.66 dl / g prepared above and 1 part by weight of crystalline spherical silica particles with an average particle size of 2.5 μm and amorphous silica coated on the surface (inorganic filler x) were mixed evenly and fed into a twin-screw extruder together. The mixture was vacuumed and subjected to filament making, cooling, pelletizing and drying to obtain a functional masterbatch X with an intrinsic viscosity of 0.65 dl / g. The functional masterbatch Z had the same composition as the functional masterbatch X.
[0164] 35 parts by weight of functional masterbatch X with an intrinsic viscosity of 0.65 dl / g and 65 parts by weight of pure polyester resin with an intrinsic viscosity of 0.67 dl / g (A1 layer), 28 parts by weight of functional masterbatch Y with an intrinsic viscosity of 0.62 dl / g and 72 parts by weight of pure polyester resin with an intrinsic viscosity of 0.67 dl / g (B layer), 22 parts by weight of functional masterbatch Z with an intrinsic viscosity of 0.65 dl / g and 78 parts by weight of pure polyester resin with an intrinsic viscosity of 0.67 dl / g (A2 layer) were mixed in advance and sent to the corresponding melt extrusion system for extrusion at a temperature of 275°C. The film is melt-extruded, enters a three-layer die for co-extrusion, and is cast onto a casting roll to form an A1 / B / A2 structure extruded casting sheet; the casting sheet is longitudinally stretched, the longitudinal stretching temperature is 75°C to 87°C, and the longitudinal stretching ratio is 2.9; the longitudinally stretched sheet is transversely stretched, the transverse stretching temperature is 108°C to 130°C, and the transverse stretching ratio is 3.5; the stretched film is shaped and cooled, and the shaping temperature is 240°C; the film is then cooled, pulled, and rolled to obtain a biaxially oriented polyester film with a thickness of 175 μm, wherein the A1 layer accounts for 8% of the total thickness, and the A2 layer accounts for 8% of the total thickness.
[0165] Example 10
[0166] Preparation of modified polyester:
[0167] According to the molar ratio of dibasic acid to ethylene glycol of 1:1.3, the addition amount of ethylene glycol antimony is 180ppm, and the addition amount of triphenyl phosphate is 80ppm. Among them, the content of 4-(3,5-dicarboxyphenoxy)phthalic acid, 4,4-propanediyldioxydibenzoic acid, 3,5-di(p-carboxyphenyl)benzoic acid, and terephthalic acid in the dibasic acid relative to the total dicarboxylic acid components is: X1=12mol%, X2=8mol%, X3=10mol%, X4=10mol%, X5=10mol%, X6=10mol%, X7=10mol%, X8=10mol%, X9=10mol%, X10=10mol%, X110=10mol%, X120=10mol%, X130=10mol%, X140=10mol%, X150=10mol%, X160=10mol%, X170=10mol%, X180=10mol%, X190=10mol%, X210=10mol%, X220=10mol%, X23 ... =20 mol%, X4=60 mol%, after the above are evenly mixed, added into a polyester synthesis reactor, beaten for 15 minutes, and nitrogen protection is introduced, and esterification is carried out at 236°C ~ 262°C, 265KPa for 3h; after the esterification is completed, vacuum is turned on, and condensation reaction is carried out at 265°C ~ 282°C, 30Pa for 5h, and after silk making, cooling, pelletizing and drying, a modified polyester with a characteristic viscosity of 0.69dl / g is obtained.
[0168] Functional masterbatch Y preparation:
[0169] 99 parts by weight of the modified polyester with a characteristic viscosity of 0.69 dl / g prepared above and 1 part by weight of crystalline spherical silica particles (inorganic filler y) with an average particle size of 0.8 μm were mixed evenly and fed into a twin-screw extruder together. The vacuum was turned on, and the functional masterbatch Y with a characteristic viscosity of 0.66 dl / g was obtained through filament making, cooling, pelletizing and drying.
[0170] Functional masterbatch X / functional masterbatch Z preparation:
[0171] 99.4 parts by weight of the modified polyester with an intrinsic viscosity of 0.69 dl / g prepared above and 0.6 parts by weight of crystalline spherical silica particles with an average particle size of 2.8 μm and amorphous silica coated on the surface (inorganic filler x) were mixed evenly and fed into a twin-screw extruder together. The mixture was vacuumed and subjected to filament making, cooling, pelletizing and drying to obtain a functional masterbatch X with an intrinsic viscosity of 0.67 dl / g. The functional masterbatch Z had the same composition as the functional masterbatch X.
[0172] 38 parts by weight of functional masterbatch X with an intrinsic viscosity of 0.67 dl / g and 62 parts by weight of pure polyester resin with an intrinsic viscosity of 0.67 dl / g (A1 layer), 35 parts by weight of functional masterbatch Y with an intrinsic viscosity of 0.66 dl / g and 65 parts by weight of pure polyester resin with an intrinsic viscosity of 0.67 dl / g (B layer), 25 parts by weight of functional masterbatch Z with an intrinsic viscosity of 0.67 dl / g and 75 parts by weight of pure polyester resin with an intrinsic viscosity of 0.67 dl / g (A2 layer) were mixed in advance and sent to the corresponding melt extrusion system for extrusion at a temperature of 280°C. The film is melt-extruded, enters a three-layer die for co-extrusion, and is cast onto a casting roll to form an A1 / B / A2 structure extruded casting sheet; the casting sheet is longitudinally stretched, the longitudinal stretching temperature is 75°C to 87°C, and the longitudinal stretching ratio is 2.7; the longitudinally stretched sheet is transversely stretched, the transverse stretching temperature is 108°C to 130°C, and the transverse stretching ratio is 3.3; the stretched film is shaped and cooled, and the shaping temperature is 243°C; the film is then cooled, pulled, and rolled to obtain a biaxially oriented polyester film with a thickness of 188 μm, wherein the A1 layer accounts for 3% of the total thickness, and the A2 layer accounts for 3% of the total thickness.
[0173] Comparative Example 1
[0174] 10 parts by weight of a common silica polyester masterbatch with an intrinsic viscosity of 0.58 dl / g, an average particle size of 0.3 μm, and a concentration of 10% and 90 parts by weight of a pure polyester resin with an intrinsic viscosity of 0.62 dl / g (A1 layer), 5 parts by weight of a common silica polyester masterbatch with an intrinsic viscosity of 0.56 dl / g, an average particle size of 0.03 μm, and a concentration of 15% and 95 parts by weight of a pure polyester resin with an intrinsic viscosity of 0.62 dl / g (B layer), 5 parts by weight of a common silica polyester masterbatch with an intrinsic viscosity of 0.58 dl / g, an average particle size of 0.3 μm, and a concentration of 10% and 95 parts by weight of a pure polyester resin with an intrinsic viscosity of 0.62 dl / g The resin (A2 layer) is mixed and processed in advance; it is sent to the corresponding melt extrusion system, melt-extruded at a temperature of 260°C, enters a three-layer die for co-extrusion, and is cast onto a casting roll to form an A1 / B / A2 structure extruded casting; the casting is longitudinally stretched at a longitudinal stretching temperature of 75°C to 87°C and a longitudinal stretching ratio of 3.8; the longitudinally stretched film is transversely stretched at a transverse stretching temperature of 108°C to 130°C and a transverse stretching ratio of 5.6; the stretched film is shaped and cooled at a shaping temperature of 220°C; the film is then cooled, pulled and rolled to obtain a biaxially oriented polyester film with a thickness of 12 μm, wherein the A1 layer accounts for 29% of the total thickness and the A2 layer accounts for 29% of the total thickness.
[0175] Comparative Example 2
[0176] 25 parts by weight of a common silica polyester masterbatch with an intrinsic viscosity of 0.64 dl / g, an average particle size of 1.5 μm, and a concentration of 3.5% and 75 parts by weight of a pure polyester resin with an intrinsic viscosity of 0.65 dl / g (A1 layer), 20 parts by weight of a common silica polyester masterbatch with an intrinsic viscosity of 0.62 dl / g, an average particle size of 0.3 μm, and a concentration of 7% and 80 parts by weight of a pure polyester resin with an intrinsic viscosity of 0.65 dl / g (B layer), 15 parts by weight of a common silica polyester masterbatch with an intrinsic viscosity of 0.64 dl / g, an average particle size of 1.5 μm, and a concentration of 3.5% and 85 parts by weight of a pure polyester resin with an intrinsic viscosity of 0.65 dl / g The ester resin (A2 layer) is mixed and treated in advance, and then sent to the corresponding melt extrusion system for melt extrusion at a temperature of 275°C, enters a three-layer die for co-extrusion, and is cast onto a casting roll to form an A1 / B / A2 structure extruded casting; the casting is longitudinally stretched at a longitudinal stretching temperature of 75°C to 87°C and a longitudinal stretching ratio of 3.3; the longitudinally stretched film is transversely stretched at a transverse stretching temperature of 108°C to 130°C and a transverse stretching ratio of 4.8; the stretched film is shaped and cooled at a shaping temperature of 230°C; the film is then cooled, pulled and rolled to obtain a biaxially oriented polyester film with a thickness of 50 μm, wherein the A1 layer accounts for 16% of the total thickness and the A2 layer accounts for 16% of the total thickness.
[0177] Comparative Example 3
[0178] 30 parts by weight of a common silica polyester masterbatch with an intrinsic viscosity of 0.64 dl / g, an average particle size of 2 μm, and a concentration of 4% and 70 parts by weight of a pure polyester resin with an intrinsic viscosity of 0.66 dl / g (A1 layer), 25 parts by weight of a common silica polyester masterbatch with an intrinsic viscosity of 0.64 dl / g, an average particle size of 0.8 μm, and a concentration of 4% and 75 parts by weight of a pure polyester resin with an intrinsic viscosity of 0.66 dl / g (B layer), 20 parts by weight of a common silica polyester masterbatch with an intrinsic viscosity of 0.64 dl / g, an average particle size of 2 μm, and a concentration of 4% and 80 parts by weight of a pure polyester resin with an intrinsic viscosity of 0.66 dl / g (A2 layer) 2 layers), pre-mixed and other treatments; sent to the corresponding melt extrusion system, melt extruded at a temperature of 275°C, entered the three-layer die head for co-extrusion, and cast onto the casting roll to form an A1 / B / A2 structure extruded casting; the casting was longitudinally stretched at a longitudinal stretching temperature of 75°C to 87°C and a longitudinal stretching ratio of 3.2; the longitudinally stretched film was transversely stretched at a transverse stretching temperature of 108°C to 130°C and a transverse stretching ratio of 4.6; the stretched film was shaped and cooled at a shaping temperature of 235°C; the film was then cooled, pulled and rolled to obtain a biaxially oriented polyester film with a thickness of 100μm, wherein the A1 layer accounts for 15% of the total thickness and the A2 layer accounts for 15% of the total thickness.
[0179] Table 1 Specific implementation effects
[0180]
[0181]
[0182] Thickness test method: GB / T 33399-2016.
[0183] Thermal performance: Take a small shaft sample with a width of 1300 and a length of 500m, pass it through the machine, and evaluate the dynamic thermal performance. Machine conditions: Set the winding tension to 160N / m, the oven temperature to 80℃ / 100℃ / 130℃ / 150℃ / 135℃ / 115℃ / 100℃ / 80℃, the length of each oven section to 4m, the speed to 60m / min, and set 2 horizontal guide rollers at 3m from the oven exit, with a vertical distance of 1.5m between the two rollers. During the machine process, the inspector's line of sight forms a 45° angle with the film surface, and a strong light flashlight (model: RJW7102A / LT, Ocean King Lighting Technology Co., Ltd.) is used to move left and right to observe carefully. At the same time, take a 1m long sample of the small shaft after passing the machine, place it on a horizontal marble platform, and the inspector's line of sight forms a 0° angle with the film surface, and a strong light flashlight (model: RJW7102A / LT, Ocean King Lighting Technology Co., Ltd.) is used to move left and right to observe carefully. During the process of passing through the machine, there is no longitudinal unevenness on the membrane surface, and the sample on the marble platform is completely in contact with the marble tabletop without ups and downs, indicating excellent thermal performance, recorded as "◎". During the process of passing through the machine, there are n (quantity)>1 longitudinal unevenness, or n (quantity)>1 ups and downs between the sample on the marble platform and the marble tabletop, indicating poor thermal performance, recorded as "×".
[0184] Scratches / abrasions: Take a full-width film with a length of about 1m as a sample, use a three-wavelength lamp or a strong light lamp, with the angle between the light and the film surface at about 45°, and the inspector's line of sight facing the light spot of the film at a distance of about 30cm. Use light transmission and reflection to visually inspect the film surface scratches / abrasions of the sample, and make statistics. If there is no scratch / abrasions on the film surface, record "Δ". If there is any scratch / abrasions, record "×".
[0185] By comparing Example 1 with Comparative Example 1, Example 5 with Comparative Example 2, and Example 7 with Comparative Example 3, it can be seen that under the same conditions of polyester film thickness, film making process, inorganic particle size, added concentration, etc., the thermal performance and scratch / scratch resistance of the biaxially oriented polyester film of the present invention are significantly better than those of ordinary polyester films.
[0186] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
[0187] Although the present invention has been disclosed as above with preferred embodiments, it is not intended to limit the present invention. A person with ordinary knowledge in the technical field to which the present invention belongs may make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the protection scope of the present invention shall be determined by the definition of the claims.
Claims
1. A biaxially oriented polyester film comprising three polyester resin layers A1 / B / A2, characterized in that: The A1 layer includes the following materials in parts by weight: Functional masterbatch X10 to 50 parts by weight 50 to 90 parts by weight of pure polyester resin; The functional masterbatch X comprises the following substances in parts by weight: Inorganic filler x 0.3 to 10 parts by weight 90 to 99.7 parts by weight of modified polyester, Wherein, the inorganic filler x is crystalline spherical silica particles coated with amorphous silica on the surface, and the average particle size is 0.3 μm to 3 μm; Layer B includes the following materials in parts by weight: Functional masterbatch Y 5 to 40 parts by weight 60 to 95 parts by weight of pure polyester resin; The functional masterbatch Y is composed of: Inorganic filler y 1 to 15 parts by weight 85 to 99 parts by weight of modified polyester, Wherein, the inorganic filler y is crystalline spherical silica particles with an average particle size of 0.03 μm to 1 μm; The A2 layer includes the following materials in parts by weight: Functional masterbatch Z 5 to 30 parts by weight 70 to 95 parts by weight of pure polyester resin; The functional masterbatch Z has the same composition as the functional masterbatch X; The modified polyester adopts 4-(3,5-dicarboxyphenoxy)phthalic acid, 4,4-propanediyldioxydibenzoic acid, 3,5-di(p-carboxyphenyl)benzoic acid, and terephthalic acid; definition: X1 is the content ratio of 4-(3,5-dicarboxyphenoxy)phthalic acid component relative to the total dicarboxylic acid components in the modified polyester; X2 is the content ratio of 4,4-propanediyldioxydibenzoic acid component relative to the total dicarboxylic acid components; X3 is the content ratio of 3,5-di(p-carboxyphenyl)benzoic acid component to the total dicarboxylic acid components; X4 is the content ratio of terephthalic acid component to the total dicarboxylic acid components; X1, X2, X3, and X4 satisfy the following relationship: 5 mol%≤X1≤15 mol% 2 mol%≤X2≤10 mol% 3 mol%≤X3≤25 mol% 50 mol%≤X4≤90 mol% X1+X2+X3+X4=100 mol%.
2. The biaxially oriented polyester film according to claim 1, characterized in that: The biaxially oriented polyester film has a thickness of 12 μm to 188 μm.
3. The biaxially oriented polyester film according to claim 2, characterized in that: The biaxially oriented polyester film contains three polyester resin layers A1 / B / A2, wherein the A1 layer accounts for 3% to 29% of the total thickness, and the A2 layer accounts for 3% to 29% of the total thickness; the thickness of the A1 layer and the A2 layer can be the same or different.
4. The biaxially oriented polyester film according to claim 1, characterized in that: The pure polyester resin is polyethylene terephthalate resin, and the intrinsic viscosity is 0.62 dl / g to 0.68 dl / g.
5. The biaxially oriented polyester film according to claim 1, characterized in that: The method for preparing the biaxially oriented polyester film is to mix the functional masterbatch X, the functional masterbatch Y, the functional masterbatch Z and the pure polyester resin in corresponding weight proportions in advance, send them into the corresponding melt extrusion system for extrusion, enter the three-layer co-extrusion die head, and then cast, longitudinally stretch, transversely stretch, heat-set, cool, pull and wind up to obtain the biaxially oriented polyester film.
6. The preparation method according to claim 5, characterized in that: The melt extrusion temperature is 260°C to 280°C.
7. The preparation method according to claim 5, characterized in that: The longitudinal stretching ratio is 2.7 to 3.
8.
8. The preparation method according to claim 5, characterized in that: The transverse stretching ratio is 3.3 to 5.
6.
9. The preparation method according to claim 5, characterized in that: The heat setting temperature is 220°C to 243°C.
Citation Information
Patent Citations
Gas barrier film laminate
CN101535040A
Polyester film and preparation method thereof
CN113635643A
Thermoplastic resin composition
CN119013355A
Production of thermoplastic resin
JP1990107631A
Polyester composition
JP1999092635A